Comparison of Quiet Quitting between Generation Z and Millennials among Indonesian Civil Servants - Fitria Anggraeni; Wisnu Yahdhiman Wiweka; Rukeni Rukeni; Rilla Sovitriana (Siber Nusantara Research Publisher, 2026)
The phenomenon of quiet quitting has increasingly attracted attention in the study of work behavior, including in the public sector. This study aims to identify the level of quiet quitting among Indonesia’s State Civil Apparatus (Aparatur Sipil Negara/ASN) and to compare its tendency between Generation Z and Millennials. This study employed a quantitative approach using a survey method involving 447 ASN employees from various government institutions in Indonesia. The sample was selected using non-probability sampling techniques, specifically convenience sampling and snowball sampling. The instrument used was the Quiet Quitting Scale developed by Manullang et al. (2025), and the data were analyzed using descriptive statistics and an independent samples t-test. The results showed that quiet quitting among ASN employees was at a moderate to moderately high level, with a mean total score of 185.60. In the comparative analysis, Generation Z showed a higher mean quiet quitting score (M = 191.14) than Millennials (M = 185.05). The results of the difference test indicated a significant difference between the two generational groups (p = 0.013), with a small to medium effect size (Cohen’s d = 0.336). Overall, the most prominent dimensions were work-life balance and digital impact, suggesting that quiet quitting among ASN employees more strongly reflects an adaptive strategy in response to work demands, the need to maintain personal life balance, and changes in work patterns due to digitalization. These findings confirm that quiet quitting among Indonesian ASN employees is a real phenomenon occurring across generations, with a stronger tendency among Generation Z.